FORMULASI SEDIAAN LIPSTIK DARI EKSTRAK KULIT BUAH DELIMA - Tazkianajia Asyrifa lizama Sholehan; Nurul Hidayah; Neneng Siti Silfi Ambarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pomegranate peel (Punica granatum L.) is a by-product of fruit consumption that remains underutilized, despite containing active compounds such as anthocyanins, tannins, and flavonoids with potential as a natural colorant in cosmetic products, including lipstick. This study aimed to formulate a lipstick preparation using pomegranate peel extract with extract weight variations of 3 grams (F1), 5 grams (F2), and 7 grams (F3), to analyze its physical quality characteristics, and to determine the best formula based on physical and hedonic tests. The extract was obtained through maceration using 70% ethanol as solvent, with a yield of 20%. The physical quality of the preparation was evaluated through organoleptic, pH, homogeneity, adhesion, melting point, and physical stability tests using a cycling test method. Panelist preference was assessed through hedonic test involving 20 panelists on the aspects of color, texture, and aroma, then analyzed using the Friedman test followed by the Wilcoxon Signed-Rank Test with Bonferroni correction. The results showed that all three formulas met the quality requirements for a good lipstick, with pH values ranging from 4.80 to 6.17, adhesion time of 5.30 to 6.51 seconds, and melting point of 54.50 to 62.50 degrees Celsius. The Friedman test showed a significant difference in color (p = 0.003) and aroma (p = 0.016), but not in texture (p = 0.264). Formula 3 (F3), variations 7 grams of extract, was the most preferred formula by panelists in terms of color and aroma. Thus, pomegranate peel extract is shown to have potential as a natural colorant in lipstick formulation with good physical quality characteristics.